2012
DOI: 10.1590/s1516-89132012000600006
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial effect of Anacardium Occidentale extract and cosmetic formulation development

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 17 publications
0
8
0
2
Order By: Relevance
“…Studies have described the antimicrobial activity of different parts of A. occidentale, such as the fruits [3] [10]- [15], stem bark [16]- [25], leaves [16]- [29] and gum [30] [31], but there are no reports of similar activity in the flowers.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have described the antimicrobial activity of different parts of A. occidentale, such as the fruits [3] [10]- [15], stem bark [16]- [25], leaves [16]- [29] and gum [30] [31], but there are no reports of similar activity in the flowers.…”
Section: Introductionmentioning
confidence: 99%
“…The antimicrobial activity of leaves, bark, fruit, flowers and stem exudate of Anacardium occidentale is well described in the literature (Himejima & Kubo 1991; Akinpelu 2001; Campos et al 2012; Gonçalves & Gobbo, 2012; Silva et al 2016), which was reviewed recently by Baptista et al (2018). Barbosa‐Filho et al (2015) reported the only other results known to us from wild populations in a study of a cerrado form interpreted by us as A. occidentale (see Introduction, reported by these authors as A. microcarpum ).…”
Section: Resultsmentioning
confidence: 95%
“…Gram-negative bacteria have a wall composed of several layers of peptidioglicanas, which differ in their chemical composition and consequently more complex than the wall of Gram-positives; although thicker ones show predominantly only one type of macro molecule. This shows the Gram-positive bacteria are more sensitive than the Gram-negative bacteria (Gonçalves and Gobbo, 2012). Considering the wealth of constituents present in plants, the positive antibacterial activity of the extract of cashew stem peels can be due to the presence of compounds such as tannins and alkaloids previously found in the plant, which possibly has a higher concentration compared to the leaves.…”
Section: Resultsmentioning
confidence: 96%